Chronic Traumatic Encephalopathy and the Built Environment - Kopec, Dak; Marsh, Kendall (UI Scholars Hub, 2020)
Traumatic Brain Injuries (TBIs) are often connected to the development of Chronic Traumatic Encephalopathy (CTE), a degenerative brain disease commonly found in athletes, military veterans, and others that have a history of repetitive brain trauma. This formative exploratory study looked at person-centred design techniques for a person with CTE. The person-centred design method used for this study was based on a two-tiered reductionist approach; the first tier was to identify common symptoms and concerns associated with CTE from the literature. This information provided specific symptoms that were addressed through brainstorming ideations. Each singular ideation accommodated the singular, or small cluster of symptoms, that affected a person with CTE in a residential environment. This method of understanding a health condition through its symptoms, and then designing for those symptoms can extend the practice of interior design by providing probable solutions to specific health symptoms, thereby including designers into the healthcare team. Commonly identified behavioural and physical symptoms of CTE served as the factors of analysis and thus a variable of design. The health condition symptoms became the variables of design, and each symptom was assessed through additional data obtained from the literature for environmental causality, mitigation, or accommodation. Once the outcomes were determined, each design implication was assessed for its relationship to specific design actions.